Metagenomic Analysis of Bacterial Communities and Antibiotic Resistance Genes in Penaeus monodon Biofloc-Based Aquaculture Environments - Chen, Xieyan; He, Zihao; Zhao, Jichen; Liao, Minze; Xue, Yuan; Zhou, Jianing; Hoare, Rowena; Monaghan, Sean J.; Wang, Na; Pang, Huanying; Sun, Chengbo (Frontiers in Marine Science, 2022)
Biofloc technology (BFT) is one of the most promising technologies in global aquaculture for the purpose of improving water quality, waste treatment, and disease prevention in intensive aquaculture systems. However, characterization of the microbial species and antibiotic resistance potentially present in biofloc-based aquaculture environments is needed. In this study, we used high-throughput sequencing technology to comprehensively compare the bacterial communities in mariculture ponds of Penaeus monodon (P. monodon), by testing of water, biofloc, and intestine of P. monodon. Operational taxonomic units (OTUs) cluster analysis showed that the nine samples tested divided into 45 phyla and 457 genera. Proteobacteria was the dominant bacteria in water, biofloc and prawn intestine. In biofloc and intestine, the Ruegeria (2.23–6.31%) genus represented the largest proportion of bacteria, with Marivita (14.01–20.94%) the largest group in water. Microbial functional annotation revealed that in all the samples, genes encoding metabolism were predominant. The antibiotic resistance gene annotation showed the highest absolute abundance of patB, adeF, OXA-243, and Brucella_suis_mprF from Proteobacteria. PatB (11.33–15.01%), adeF (15.79–18.16%), OXA-243 (35.65%), and Brucella_suis_mprF (10.03%) showed the highest absolute abundance of antibiotic resistance genes in water, biofloc, and intestines, respectively. These findings may greatly increase our understanding of the characteristics of the microbiota of shrimp biofloc-based aquaculture systems and the complex interactions among shrimp, ambient microflora, and environmental variables. It provides a reference basis for policy on breeding, environmental safety, and maintaining food safety in the production of P. monodon.